The Effect Of Speed Training On The Ball Dribbling Speed Of Futsal Players At The Futsal Club Thepoon Fc In Kepahiang Regency - Saputera, Rendi Pranata; Martiani, Martiani; Anggara, Deffri (Journal of Education, 2025)
This study aims to determine and analyze the effect of speed training on increasing dribbling speed in futsal players at Thepoon FC Futsal Club, Kepahiang Regency. Using a total sampling method, namely 12 futsal players at Thepoon FC Futsal Club, Kepahiang Regency. This experimental study uses a One Group Pre-test - Post-test design form, which is a pre-experimental design that contains a pre-test (test before being given treatment) and a post-test (test after being given treatment) in one group. Data collection used is using test scores. Using descriptive data analysis techniques and t-tests. The results of this study indicate that there is an effect of speed training on dribbling speed of futsal players at Thepoon FC Club, Kepahiang Regency, with a calculated t value of 2.728 while the t table is 1.796 with a significance level of α = 0.05 and dk = 12